Penerapan Model Log Linear Tiga Dimensi dalam Analisis Faktor Risiko Riwayat Sakit Maag - Wita Resfi Ananta Wita; Eujenniatul Jannah; Siti Nurhaliza; Yenni Kurniawati; Syafriandi Syafriandi (Departemen Statistika Universitas Negeri Padang, 2025)
Gastritis, or commonly known as an ulcer, is an inflammatory condition caused by excess stomach acid that irritates the stomach lining. This disease is one of the most common in Indonesia and often disrupts daily activities, especially among students who face academic pressure, stress, and irregular diet. Based on Indonesia’s Health Profile Data, gastritis ranks sixth for inpatients with 330,580 cases, 60.86% of which occur in women, and seventh for outpatients with 201,083 cases, of which 77.74% occur in women. This study aims to examine the relationship between gastritis and demographic factors using a three-dimensional log-linear model. The method analyzes interactions between categorical variables to identify the best explanatory model. Results indicate that the most appropriate model involves the interaction between place of residence, gender, and history of stomach ulcers, showing that these factors collectively influence gastritis incidence. In conclusion, gastritis is not only related to physical health but also lifestyle and demographic factors. This study underlines the importance for students to manage stress, maintain healthy eating habits, and adopt preventive measures. The urgency of this research lies in raising awareness that untreated gastritis may reduce productivity and lead to more serious health problems.